2019
DOI: 10.1039/c9gc01865d
|View full text |Cite
|
Sign up to set email alerts
|

A closed-loop and sustainable approach for the fabrication of plastic-free oil- and water-resistant paper products

Abstract: The current open-loop practices employed to render paper substrates water- and oil-repellent for packaging and non-packaging applications have generated ocean pollution and have placed daunting burdens on landfills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 30 publications
0
56
0
Order By: Relevance
“…All of the results were compensated to 100% relative humidity with nitrogen as a carrier gas (flow rate = 12 SCCM (SCCM stands for Standard cubic centimeters per minute)). The samples were prepared via our previously reported method 24 . All of these values were reported in units of g/m 2 day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the results were compensated to 100% relative humidity with nitrogen as a carrier gas (flow rate = 12 SCCM (SCCM stands for Standard cubic centimeters per minute)). The samples were prepared via our previously reported method 24 . All of these values were reported in units of g/m 2 day.…”
Section: Methodsmentioning
confidence: 99%
“…Polysaccharides and proteins are biodegradable in nature and their use for paper coating is very appealing, but they are hydrophilic in nature and hence they have poor water resistance 10,19–21 . Recently, our group has developed chitosan‐ graft ‐silicone oil coatings for paper with good water and oil repellent properties 22–26 . Silicone oil was chosen because of its relatively food safe nature and exceptional water and oil repellent properties that have been demonstrated in various coatings 27–34 .…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan-g-PDMS was synthesized by our reported literature method. [13] NMR spectrum of chitosan-g-PDMS was recorded in D 2 O and CD 3 COOD NMR solvents due to the solubility of chitosan in a slightly acidic medium. Figure S2 shows the spectra for chitosan-g-PDMS, where the peak at −0.15 ppm indicates that PDMS has been grafted onto chitosan.…”
Section: Repulpabilitymentioning
confidence: 99%
“…9 To address the above challenges, our group is actively working towards developing plastic-free, PFAS-free, costeffective water-and oil-resistant surfaces. [10][11][12][13][14][15] One of the key focus is the use of benign polydimethylsiloxane (PDMS) as an alternative to PFAS because PDMS is known for imparting water and oil repellent properties while still acceptable for food contact applications. [16][17][18][19][20][21][22] In a recent breakthrough study, we reported the fabrication of water-and grease-resistant coating using Chitosan-grafted-PDMS (Chitosan-g-PDMS), and the coated paper was 100% recyclable by washing the coating off.…”
Section: Introductionmentioning
confidence: 99%
“…Papers is a low‐cost, food‐safe, renewable and biodegradable material and is used extensively in the packaging industry 1–3 . In addition to good mechanical properties (e.g.…”
Section: Introductionmentioning
confidence: 99%